2023
DOI: 10.1037/aca0000555
|View full text |Cite
|
Sign up to set email alerts
|

Focus of attention affects togetherness experiences and body interactivity in piano duos.

Abstract: Group music-making is a socially rewarding activity that strengthens social bonds and leads to feelings of musical togetherness, that is, feelings of musical alignment and social connection. For skilled ensemble musicians, social rewards are closely tied to the aesthetic rewards that come from achieving a high-quality performance. What playing conditions encourage or discourage togetherness experiences? The purpose of this study was to show how joint and mutual attention contribute to experiences of togetherne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…Future follow-up investigations could investigate continuous ratings of togetherness feelings in singing performances, resulting from the manipulation of the sound spectral envelope, to investigate the relationship between sound envelope and togetherness. It also remains unknown how their perceived optimal match (conceptualized in terms of spectral components) relates to the broad range of togetherness feelings (resulting from the social and cognitive alignment with the co-performer that varies as the music unfolds (Bishop, 2023 ; D'Amario et al, 2023 ). Future studies based on self-reported experiences might shed more light in this respect by investigating how musicians conceptualize togetherness feelings and voice match sensation.…”
Section: Limitationsmentioning
confidence: 99%
“…Future follow-up investigations could investigate continuous ratings of togetherness feelings in singing performances, resulting from the manipulation of the sound spectral envelope, to investigate the relationship between sound envelope and togetherness. It also remains unknown how their perceived optimal match (conceptualized in terms of spectral components) relates to the broad range of togetherness feelings (resulting from the social and cognitive alignment with the co-performer that varies as the music unfolds (Bishop, 2023 ; D'Amario et al, 2023 ). Future studies based on self-reported experiences might shed more light in this respect by investigating how musicians conceptualize togetherness feelings and voice match sensation.…”
Section: Limitationsmentioning
confidence: 99%